STUDIES ON THE CORNEA : III. The Fine Structure of the Frog Cornea and the Uptake and Transport of Colloidal Particles by the Cornea in vivo - Kaye, Gordon I. (The Rockefeller University Press, 1962)
The fine structure of the frog cornea has been studied and compared with that of the rabbit cornea (1, 2) particularly in relation to the uptake and transport of colloidal particles. The frog corneal endothelium does not possess a terminal bar and the fluid space of the intercellular space is apparently continuous with that of the anterior chamber. Colloidal markers (ThO(2), Fe(2)O(3)) placed in the anterior chamber pass down the intercellular space into the cornea. Markers injected intrastromally diffuse freely in the stroma and Descemet's membrane but pass across the endothelium only via membrane-bounded vesicles. These results are compared with those of similar experiments in the rabbit and it is concluded that the primary pathway for the passage of materials into the cornea is intercellular and that the pinocytotic pathway of the rabbit corneal endothelium (Kaye and Pappas; Kaye et al.) is an adaptation to the presence of a terminal bar. The significance of the separation of inward and outward pathways in terms of corneal metabolism is considered.